Pengembangan Game Edukasi Berbasis Blooket untuk Meningkatkan Keterampilan Menulis Teks Berita - Srimiati, Srimiati; Kusumawati, Tri Indah (GERAM (Gerakan Aktif Menulis), 2026)
This study aims to develop an educational game using the Blooket platform to improve the news writing skills of seventh-grade students at SMP PAB 21 Pematang Johar. This research applies the Research and Development (R&D) approach through the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. Meanwhile, data collection is carried out using observation, interviews, questionnaires, and tests. The instruments used in this study include validation sheets from media experts, material experts, language experts, response questionnaires from teachers and students, as well as pretests, posttest and N-Gain tests. This study involved 25 students from the seventh grade at SMP PAB 21 Pematang Johar. The findings of this study indicate that Blooket-based educational games received validation of 97% from media experts, 91% from material experts, and 85% from language experts, all of which fall into the very feasible category. Student responses to the media reached 88% and teacher responses were around 90%, also in the very good category. In addition, the N-Gain analysis yielded a score of 0.81 with a percentage of 81.11%, classified in the high group. This indicates that Blooket-based educational games are effective in improving the news text writing skills of seventh-grade students at SMP PAB 21 Pematang Johar.